2019
DOI: 10.3389/fpsyt.2019.00423
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Resistance: Is It a Requisite for Increased Cytokine Production in Depression? A Systematic Review and Meta-Analysis

Abstract: Background: Glucocorticoid resistance—reduced function of the glucocorticoid receptor (GR)—is seen in many depressed patients. It is argued that this resistance to glucocorticoids leads to failure of normal feedback regulation on the immune system. High levels of pro-inflammatory cytokines result. Purpose: We sought to identify evidence supporting or refuting a link between glucocorticoid resistance and immune dysregulation in depression and to summarize retrieved evidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 78 publications
0
49
0
1
Order By: Relevance
“…While the concept of reduced GR function and expression leading to 'glucocorticoid resistance' in depression has been extensively discussed before [51][52][53][54][55] , including for TRD patients [56][57][58] , the present study shows that reduced GR mRNA expression alone cannot fully explain the increased inflammation. Indeed the aforementioned study by Mellon et al 21 found upregulation of immune pathways in mononuclear cells from depressed patients in the absence of changes in GR function, and our own clinical meta-analysis on this topic has found only limited evidence linking 'glucocorticoid resistance' to inflammation 59 . Furthermore, it is important to emphasise here the additional confounding effects of antidepressant treatment.…”
Section: Discussionmentioning
confidence: 80%
“…While the concept of reduced GR function and expression leading to 'glucocorticoid resistance' in depression has been extensively discussed before [51][52][53][54][55] , including for TRD patients [56][57][58] , the present study shows that reduced GR mRNA expression alone cannot fully explain the increased inflammation. Indeed the aforementioned study by Mellon et al 21 found upregulation of immune pathways in mononuclear cells from depressed patients in the absence of changes in GR function, and our own clinical meta-analysis on this topic has found only limited evidence linking 'glucocorticoid resistance' to inflammation 59 . Furthermore, it is important to emphasise here the additional confounding effects of antidepressant treatment.…”
Section: Discussionmentioning
confidence: 80%
“…In support of that, elevated cortisol levels, GR insensitivity and dysregulation of the HPA axis have been consistently correlated with the inflammatory manifestations during MDD (Turecki and Meaney, 2016). In a recent single-nucleus RNA sequencing study of PFC in patients with MDD, co-chaperones of GRs (Heat shock protein 90 and FKBP5) were downregulated (Nagy et al, 2020), whereas in a systematic meta-analysis, it was demonstrated that increased inflammation (TNF-a, IL-6) is correlated with glucocorticoid resistance and elevated levels of cortisol in patients with MDD (Perrin et al, 2019).…”
Section: Integrating Neuroimmune Systems In Mental Disorder Pathogenementioning
confidence: 99%
“…Moreover, disruption of the intestinal barrier and its increased permeability may be caused by broad range of other stressors including immune, intestinal microbiota-related and environmental factors namely, pro-inflammatory cytokines, i.e., IFN-γ (113), TNF-α (114,115), IL-1β (116), further, NF-κB (117), O&NS (112,118), infections (119,120), abnormalities in gut flora composition such as dysbiosis and small intestine bacterial overgrowth (SIBO) (47,121,122), alcohol (47,(123)(124)(125), heat stress (126), food additives and pesticides (127)(128)(129)(130)(131)(132), prolonged strenuous exercise (133,134), specific medication including non-steroidal anti-inflammatory drugs (NSAID) (135,136) or antibiotics (137-140) ( Figure 1). Furthermore, psychological stress, MDD and chronic inflammatory disorders are often accompanied by hypercortisolemia which when prolonged, may lead to glucocorticoid (GKK) receptors resistance (141). This might be another crucial aspect in the context of increased intestinal permeability in MDD since it has been demonstrated that GKK…”
Section: From Gut-derived Lipopolysaccharides To Depression Via the "mentioning
confidence: 99%